Double layers optimal scheduling of distribution networks and photovoltaic charging and storage station cluster based on leader follower game theory - Zixuan Liu; Jun Wu; Ruijin Zhu; Dewen Kong; Hao Guo (Scientific Reports)
Abstract The paper addresses the economic operation optimization problem of photovoltaic charging-swapping-storage integrated stations (PCSSIS) in high-penetration distribution networks. It proposes a dual-layer optimization scheduling model for PCSSIS clusters and distribution network systems. Firstly, a master–slave game model is constructed. The upper layer takes the high-penetration distribution network as the decision-making entity and aims to maximize its own revenue while considering the energy trading of PCSSIS. The lower layer takes PCSSIS as the decision-making entity, and PCSSIS adjusts energy flow and optimizes revenue based on the internal electricity price provided by the upper-layer distribution network. Secondly, the differential evolution algorithm and GUROBI solver are used to solve for the maximum revenue, internal electricity price, and electricity consumption of PCSSIS and the distribution network. Finally, the effectiveness of the proposed strategy is verified through case studies and simulations.